Online Learning Implementation and Challenges during Covid-19 Pandemic: English Lecturers’ Perspective in Indonesia - Tira Nur Fitria; Afdaleni; Nurmala Elmin Simbolon; Ida Bagus Putu Suamba (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study investigates the English lecturers’ perspective on the implementation and their challenges (difficulties) in online learning during the Covid-19 pandemic. This research is qualitative descriptive. There are 115 English lecturers from various state and private higher institutions in Indonesia are involved in this research. The result analysis shows that most English lecturers implement online learning during 4 semesters, and the dominant applications used are Zoom Meeting, WhatsApp, Google Meet, Institutional E-Learning, and YouTube. During conducting online learning, 1) they have the flexibility of place and time in teaching, 2) they have the freedom to choose and use the type of e-learning app and they feel satisfied with the use of application features to support online lectures. But, they need more time to prepare materials, use more materials, use creative and interesting materials also use interesting and different teaching methods. The English lecturers also face difficulties during conducting online learning such as 1) difficulty to master the class and control students. 2) the students are not more participative, enthusiastic, and interactive, 3) difficulty determining/assigning assignments/projects, and 4) difficulty holding mid-term and end-of-semester exams online both written exams and oral exams. 5) difficulty in evaluating/assessing students during online learning. 6) feel worried about students' abilities and grades. Sometimes they also feel bored teaching online. Besides, they experience other various problems, such as quota and internet connection, interference with the device used, and environmental conditions, even though they don't know students more closely and personally. After conducting online learning, English lecturers feel satisfied with online lectures for several semesters, feel online learning is more interesting and challenging, but they have more teaching load in online lectures than offline even do not receive more compensation for teaching online.